A Review on Wireless Sensor Network Based Approaches for Temperature Sensing Applications - Surender Kumar (AG Volumes, 2022)
In this paper, the most current breakthroughs as well as research investigations on the cold thermal energy storage are summarized in detail (CTES). Water may be chilled or frozen to the store cooling capacity (or even the other materials as the glycol and the eutectic salts). A number of practical as well as the the thermodynamic factors, along with the availability, the relative harmlessness, and the compatibility with a broad range of the equipment for storage as well as handling, make water the storage medium of choice. Decisions including that equipment must be utilized, whether the eutectic salts are needed to boost the freezing temperatures etc. might be difficult to make. Often these decisions are not easy. There are a plethora of possibilities, yet there are no easy solutions. CTES methods should be tailored to the unique demands and limits of facility in that they are implemented.